Den liturgiske eksegese og Grundtvig - Thodberg, Christian (Grundtvig-Studier, 2000)
Grundtvig and Liturgical Exegesis By Christian Thodberg Liturgical exegesis is defined as the way in which the Church re-actualised the words and deeds of Jesus in the service of worship in trying to answer the need of the congregation for being simultaneous with the biblical events. In the Western Church this liturgical exegesis received an emphatic exposition in connection with the old series of pericopes in the roman mass and in most of protestant churches as well. Many modem preachers do not like the old lectionary because it is crammed with the stories of Jesus’ miracles which - as they say - have no relevance to churchgoers of today. Grundtvig, however, always met those stories with pleasure, because in his opinion, they dealt with Jesus’ strong deeds in the worship today in baptism and communion. And essentially the biblical readings are worked out on the Sundays before and after the old baptismal terms, either at Easter time, or on the sixth of January, or at Whitsun. Thus baptism is defined in three ways by the three old baptismal terms: on January sixth as a birth with Christ, at Easter as death and resurrection with Christ and at Pentecost as the reception of the gift of the Holy Spirit. The Western system of gospel readings in general survived the Reformation, but in the course of the seventeenth and eighteenth centuries the account of Christ’s acts of power came under critical scrutiny. They were understood as magical elements, which obscured the character of the bible as the teaching of Christianity. Parallel with this, in the context of the liturgy, the renunciation and the naming of the Devil and the word Hell was removed from the Apostles’ Creed in the baptismal rite and the Annunciation, the Resurrection and the Ascension were understood as images. As an old-fashioned believer, Grundtvig protested against all this. Christianity depended on Christ’s works of power. But despite his faith that the bible was literally God’s word, his problem was this: When and how did God’s word and Christ’s deeds of power touch him personally? Theologically, the question about the presence of God was a problem for Grundtvig throughout his life. In simple terms: Where does God speak to mel Grundtvig’s problem was solved by his famous »unparalleled discovery«, which became the hermeneutic key to his sermons. The thesis of liturgical history scholarship is that liturgical exegesis has its place already in the New Testament, and that the secondary epistles of St. Paul in connection (Ephesians, Colossians) can be rehabilitated, since they give us the key to the understanding of Jesus’ miracles in relations to baptism. In the end it points to Grundtvig’s persistent attempt to find the place where God speaks to him, where he intuitively rediscovers the early church’s understanding of the connection between Jesus’ works of power and baptism, and which thus becomes a contemporary challenge to New Testament scholarship and preaching today.